Enfoque jurídico del abuso sexual de adolescentes y su incidencia en los derechos constitucionales de las víctimas en el Ecuador - Quishpe Chariguamán, Rubén Neptalí (2015)
The criminal investigation is complicated and here's an essential task of Justice in gathering information for the respective evidence then prosecute the case. Its applications are critical and a solid collection of data will influence the acceptance of responsibility when you're in front of a process. Knowing the nature of sexual offenses, these will determine what types of research being carried out at pre judicial level, and what evidence they should act on the same level are. Media is substantial evidence for the criminal investigation and mandatory practice in the case of sexual violation; but they are optional in crimes of indecent acts. It is necessary to establish what the impact of casualties on the specific case and prove sexual penetration, after a mandatory medical examination.